Pakistan–China Strategic Partnership and Its Impact on Regional Stability - Arif (Phd), Muhammad (Kashmir Journal of Academic Research and Development, 2025)
The Pakistan-China strategic partnership has transformed to become one of the most sustainable and high-dimensional bilateral relations in the modern international politics. This joint venture is based on mutual security issues, economic interconnectedness and overlapping geopolitical interests and is therefore a decisive factor in the stabilization of the region in South Asia, Central Asia and the Indo-Pacific. The cooperation is in the areas of defense cooperation, counterterrorism, nuclear and technological assistance, and macroeconomic integration most vividly seen in the China-Pakistan Economic Corridor (CPEC). As the supporters take the partnership as a stabilizing factor with the effect of encouraging economic development and equalizing the power disparity of the regions, the opponents claim that it has exacerbated strategic competition, especially with India, and has brought about the issue of debt sustainability, regional security predicaments and militarization of the Indian Ocean. The paper examines historical, strategic, and modern aspects of the relationship between Pakistan and China, evaluating how they could affect the peace and conflict in the region as well as the multipolar order in Asia. The discussion indicates that the alloy is a stabilizing and destabilizing element, and it can lead to the development of regional connectivity and cooperation, but it can also cause the intensification of the existing geopolitical frictions.
Keywords: Pakistan-China relations; CPEC; regional stability; South Asia; strategic partnership; geopolitical rivalry; Indo-Pacific; economic integration; security cooperation